2015
DOI: 10.1104/pp.15.01174
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Foundation of Starch-to-Lipid Switch in Oleaginous Chlorella spp.

Abstract: The ability to rapidly switch the intracellular energy storage form from starch to lipids is an advantageous trait for microalgae feedstock. To probe this mechanism, we sequenced the 56.8-Mbp genome of Chlorella pyrenoidosa FACHB-9, an industrial production strain for protein, starch, and lipids. The genome exhibits positive selection and gene family expansion in lipid and carbohydrate metabolism and genes related to cell cycle and stress response. Moreover, 10 lipid metabolism genes might be originated from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
77
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(85 citation statements)
references
References 88 publications
(95 reference statements)
7
77
0
Order By: Relevance
“…Metabolic flux analysis performed in Chlorella protothecoides showed that carbon flow from acetyl-CoA to FA pools increased from 58 to 109% of glucose uptake during nitrogen-limited growth [71], indicating that algal cells substantially reorganize their metabolism to divert more acetyl-CoA towards lipid production. Increased NADPH pool in a Chlorella pyrenoidosa mutant overexpressing an A. thaliana NADH kinase (AtNADK3) has also been associated with enhanced lipid content of up to 110% [72] (Table 1). Oleaginicity is hence attributed to the presence and activity of enzymes responsible for the supply of acetyl-CoA and NADPH to FA synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic flux analysis performed in Chlorella protothecoides showed that carbon flow from acetyl-CoA to FA pools increased from 58 to 109% of glucose uptake during nitrogen-limited growth [71], indicating that algal cells substantially reorganize their metabolism to divert more acetyl-CoA towards lipid production. Increased NADPH pool in a Chlorella pyrenoidosa mutant overexpressing an A. thaliana NADH kinase (AtNADK3) has also been associated with enhanced lipid content of up to 110% [72] (Table 1). Oleaginicity is hence attributed to the presence and activity of enzymes responsible for the supply of acetyl-CoA and NADPH to FA synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they can be cultivated in wastewater and saltwater systems which will not directly compete with resources necessary for agricultural food production56. When cultivated under stressful conditions such as nitrogen depletion (N-depletion), photosynthetic microalgae alter their metabolism to redirect energy towards the production and accumulation of energy-rich storage compounds such as starch and lipids789, but at the cost of diminished growth. This ability enables the microalgae to survive adverse environmental changes as the energy deposits can be easily mobilized when growth conditions are restored10.…”
mentioning
confidence: 99%
“…Traditionally, Nannochloropsis oceanica strains are favored for studying lipid accumulation131415, and the freshwater microalgal species Chlamydomonas reinhardtii 1617 and Chlorella vulgaris 81819 are most commonly studied for starch accumulation. The latter two species have thus far been cultivated mixotrophically or heterotrophically with the addition of organic carbon such as acetate and glucose20.…”
mentioning
confidence: 99%
“…By contrast, knockout of CrNRR1, a specific TAG regulator for nitrogen deprivation, resulted in 50% decrease in TAG content in C. reinhardtii under nitrogen deprivation conditions (Boyle et al, 2012). A recent whole genome and transcriptome study reconstructed the central carbon metabolism of Chlorella pyrenoidosa, including lipid biosynthesis pathways, and suggested NAD(H) kinase3 (NADK3) controlled NADPH supply and contributed to lipid production in this alga (Fan et al, 2015). Overexpression of an Arabidopsis NAD(H) kinase in C. pyrenoidosa enhanced cellular lipid content effectively by 110.4% without slowing down growth rate (Fan et al, 2015), representing a significant increase in lipid production in industrial-relevant algal strains.…”
Section: Transcription Factor Genes and Other Regulatorsmentioning
confidence: 87%
“…A recent whole genome and transcriptome study reconstructed the central carbon metabolism of Chlorella pyrenoidosa, including lipid biosynthesis pathways, and suggested NAD(H) kinase3 (NADK3) controlled NADPH supply and contributed to lipid production in this alga (Fan et al, 2015). Overexpression of an Arabidopsis NAD(H) kinase in C. pyrenoidosa enhanced cellular lipid content effectively by 110.4% without slowing down growth rate (Fan et al, 2015), representing a significant increase in lipid production in industrial-relevant algal strains. These studies confirm the potential of omics studies and pathway modeling in identification of metabolic switches for maximizing TAG production in algae.…”
Section: Transcription Factor Genes and Other Regulatorsmentioning
confidence: 99%